Meningkatkan kemampuan membaca melalui media papan baca berputar pada siswa kelas 1 sekolah dasar - Sholihah, Nur Hidayatus (Maliki Interdisciplinary Journal, 2025)
The rotating reading board is a learning tool designed to enhance children’s reading abilities in a fun and interactive way. This media consists of three rotating panels containing vowels, consonants, and syllables that can be combined to form simple words. In addition to improving phonetic and reading skills, the tool also fosters overall language development, including listening, speaking, reading, and writing. Its main advantage lies in the playful elements that increase children’s enthusiasm for learning. This study employs a descriptive qualitative method with data collected through literature reviews from books and academic journals. The findings suggest that the rotating reading board is an effective alternative for enhancing children’s reading skills.